WORKPLACE DIVERSITY MANAGEMENT AND RUSSIA LANGUAGE LEARNING: A STUDY OF RUSSIAN EMBASSY IN NIGERIA - Ugo Chuks Okolie; Eseohe Glory Okoedion (Business Education Program of Universitas Pendidikan Indonesia, 2023)
This study investigates how diversity management affects Russian language instruction at the Russian Embassy in Nigeria. Data gathered from 50 Nigerian employees working in the Russian Embassy in Lagos and Abuja was used for this study and the sample size was not based on gender bias. Questionnaire was distributed randomly, and the data were analyzed using percentage and frequency, mean, standard deviation, Pearson's product moment correlation, and multiple regression analysis with the help of the Statistical Package of Social Sciences (SPSS version 23.0, 2020). According to the study's findings, diversity management significantly improved organizational learning effectiveness and the learning of Russian language in the Russian Embassy in Lagos and Abuja. The study's findings, which include a recommendation that the management of the Russian Embassy in Nigeria should make available a platform for the use of films, audios, music, or songs as learning tools for the Russian language, will motivate employees and subsequently improve their language skills. The study demonstrated that diversity management can improve organizational learning effectiveness, bring about competitive advantage, and enhance Russian language learning in Nigeria. Therefore, the management at the Russian Embassy in Nigeria will find this study useful. The study will, nevertheless, be useful for those who wish to learn more about workplace diversity and how to handle it.